Digital Innovation in Early Detection of Student Burnout: Development and Validation of the Android-Based Assessment Application BURNTES - Romiaty Romiaty; Fendahapsari Singgih Sendayu; Wenti Marseani Putri (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
Academic burnout among secondary school students has become an increasing concern, particularly in digital learning environments where systematic assessment and early detection remain limited. This study aimed to develop and validate BURNTES (Burnout Test for Students), an Android-based burnout assessment application designed to support guidance and counseling services in Indonesian secondary schools. Using a research and development approach, the study adopted the 4D model (Define, Design, Develop, and Disseminate). Data were collected through needs analysis, expert judgment, small-group trials, and preliminary effectiveness testing. Content validity was evaluated by five experts using Aiken’s V index, yielding a coefficient of 0.67, which indicates high and acceptable validity. Practicality testing involving 20 students and three counseling teachers resulted in a usability score of 88.7%, categorized as very practical. The effectiveness of BURNTES was examined using the Wilcoxon Signed-Rank Test, demonstrating a significant improvement in students’ ability to detect and understand burnout symptoms after application use (p < 0.001), supported by a large effect size (r = 0.873). These findings indicate that BURNTES is a valid, practical, and effective digital assessment tool that enhances the accuracy and efficiency of academic burnout detection and supports data-driven early intervention in school counseling contexts.